(untitled) (Journal of Nobel Medical College, 2020)
Background: An avulsion fracture of posterior cruciate ligament from tibial attachment is more common in younger age group. It should be fixed otherwise it may lead to secondary changes in knee. Various techniques and approaches are available to fix posterior cruciate ligament avulsion. Different biomechanical studies have shown that, results both open and arthroscopic methods of fixation of posterior cruciate ligament avulsion by screws are comparable. The purpose of study is to evaluate functional and clinical outcome of open reduction and fixation of posterior cruciate ligament avulsion injury through posteromedial approach. Materials and Methods: The study enrolled 19 cases of isolated posterior cruciate ligament avulsion injury with mean age of 33.21±9.07 year. All cases were treated by open reduction and internal fixation through modified posterior approach. The patients having duration of injury more than 12 weeks were excluded. The minimum follow up duration was 12 months. Results were assessed clinically and radiologically. Final functional outcome was assessed using the Lysholm scoring for knee. Results: The mean duration of follow up was 14±1.85 months. All patients achieved union at 3months. At final follow up the mean range of motion was 125.42±6.37 degree (range 110 to 135 degree) without any extensor lag. The functional outcome assessed by Lysholm scoring system was excellent in 15 cases and good in 4 cases. Conclusion: Open reduction and internal fixation with early range of motion exercises provides good clinical outcome and stable knee.